WASTE MANAGEMENT ON FISHING VASSELS BASED AT BITUNG OCEANIC FISHING PORT - Mahendra Jaya, Made; Tanjung Putri, Elsari; F. Hutapea, Roma Yuli; A. Tauladani, Saeful; Katili, Lidya; Suratna, Suratna; Muddin, Imam; Rislam, M. Nasril (Politeknik Kelautan dan Perikanan Dumai, 2025)
Fisheries activities at the Bitung Ocean Fishing Port (PPS) have the potential to cause pollution, particularly due to waste generated by fishing vessels. Waste generated on board is categorized into two types: organic and inorganic waste. Information on waste management aboard fishing vessels based at PPS Bitung is minimal and very limited. The aims is to study waste management aboard these vessels and analyze waste management strategies. The research was conducted from August to November 2024 at PPS Bitung. Data were collected using survey methods and interviews with respondents selected through purposive sampling. Data were collected using survey methods and interviews with respondents selected by purposive sampling. Data analysis used descriptive methods with a qualitative approach, and waste management strategies were analysed using SWOT analysis. The results showed that the categories of waste generated by fishing vessels include wet waste (food), which is directly dumped into the sea, and dry waste such as plastic, bottles, cloth, glass, and metal, which are collected first. Dry waste management is carried out in two ways, namely without sorting and with sorting. The waste management strategy on board fishing vessels in PPS Bitung is designed to increase environmental awareness and waste management efficiency through an integrated approach. The combination of education, regulation and partnership provides a comprehensive solution to minimize the environmental impact of waste and increase the active participation of crew members in waste management. Consistent implementation of this strategy can serve as a model for sustainable waste management in the fisheries sector.